Penerapan Terapi Akupressur dalam Upaya Menurunkan Tekanan Darah pada Lansia Dengan Hipertensi di Panti Sosial Tresna Werdha 2 Cengkareng - Siti Nur Asma Fadhilah; Nandila Annisa Susandy; Vivi Rachmawati; Lily Herlinah (Institut Nalanda, 2026)
Hypertension is a common health problem among the elderly and increases the risk of complications. Management programs in nursing homes are not yet optimal due to limited physical activity among residents. Therefore, safe, simple, and self-care nonpharmacological interventions are needed, such as acupressure therapy. To determine the application of acupressure therapy in reducing blood pressure among elderly patients with hypertension at Tresna Werdha Budi Mulia 2 Social Home, Cengkareng. This study used a case study design. The intervention was conducted from January 13–15, 2026. Acupressure therapy was applied for approximately 30 minutes daily at specific points. Blood pressure was measured before and after the intervention using a sphygmomanometer. The results showed a decrease in blood pressure after three days of acupressure therapy. The average reduction in systolic blood pressure was ±11.4 mmHg and diastolic blood pressure was ±5.3 mmHg. Participants also reported reduced neck stiffness, improved sleep quality, and increased relaxation. Acupressure therapy is effective in lowering blood pressure among elderly patients with hypertension and can be used as a safe, simple, and applicable nonpharmacological nursing intervention in nursing home settings.